An Analysis of Grammatical Errors in Writing Thesis Proposal of English Department Students in Mulawarman University in the Academic Year 2018/2019 - Lidya Ayu Permatasari; Ventje Kalukar; Ida Wardani (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2019)
The purposes of the study were (1) To find out the types of grammatical error made by English Department students in writing thesis proposal and (2) To know the most dominant grammatical error made by English Department students in writing thesis proposal. The subjects of this study were the eighth semester students of English Department. The researcher used the students’ thesis proposals as the instrument which had a total of 20 thesis proposals. The data was collected through quantitaive-qualitative methods. Therefore, this study used document analysis. The findings showed that the students of English Department made errors in singular-plural noun, word form, subject-verb agreement, verb tense, and verb form in writing thesis proposal. There were 47 errors in singular-plural noun or 12.46%, 3 errors in word form or 0.80%, 238 errors in subject-verb agreement or 63.12%, 58 errors in verb tense or 15.39%, and 31 errors in verb form or 8.23%. Therefore, the most dominant error that the students made was subject-verb agreement (238 errors or 63.12%).